(untitled) (Zia e Tahqeeq, 2025)
Hadith is a significant source of Islamic Shariah. Therefore, both jurists and muhadithin attempted to preserve it since the early period of Islam. It seems that sometime two or more Ahadith’s are presenting a certain meaning or an obligation, but in opposite perspective. One of them is about doing and second one neglects it. In this case, muhadithin have made rules and regulations to harmonies them by eradicating the contradictions. It is called Ilm-ul-Mukhtalif-ul-hadith. In this way, three steps are followed to resolve the meaning of that Ahadith. So, the third step is Tarjih (Science of preference). Hafiz Ibn Hajar, a well-known traditionist, used this term in his book Fath al-bari at many places. This article aims to analyze Ibn Hajar’s method of preference applied in this writings in case of two conflicting traditions or narrations.